Pengembangan Bahan Ajar Interaktif BerbantuanCanva Terintegrasi Pembelajaran Matematika Berbasis Masalah Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Nurhalimah Nurhalimah; Amprasto Amprasto; Sri Dewi Nirmala (Publikasi Indonesia, 2025)
The Merdeka Curriculum is an educational initiative that aims to provide greater flexibility and relevance in the learning process. However, the successful implementation of the Merdeka Curriculum from a pedagogical perspective requires careful preparation from various aspects. This study aims to analyze the readiness of the Merdeka Curriculum implementation from a pedagogical perspective using the literature study research method. Through analyzing various articles, reports, and related literature, this study identifies key factors that influence the readiness of the Merdeka Curriculum implementation, such as teacher readiness, educational infrastructure, and support from the government and related stakeholders. The results of the analysis show that despite the efforts made to improve the readiness of the Merdeka Curriculum implementation in the pedagogical aspect, there are still a number of challenges that need to be addressed. education. Keywords: Independent Curriculum, Pedagogical Perspective